1986
DOI: 10.1068/p150067
|View full text |Cite
|
Sign up to set email alerts
|

Acuity of Sound Localisation: A Topography of Auditory Space. III. Monaural Hearing Conditions

Abstract: A study is reported in which the acuity of azimuth and elevation discrimination under monaural listening conditions was measured. Six subjects localised a sound source (white noise through a speaker) which varied in position over a range of elevations (-40 degrees to +40 degrees) and azimuths (0 degrees to 180 degrees), at 10 degrees intervals, on the left side of the head. Monaural listening conditions were established by the fitting of an ear defender and one earmuff to the right ear. The absolute and algebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…For example, spectral cues to sound location have been invoked to account for the accuracy of localization by monaural listeners (Harris and Sergeant, 1971; Butler and Flannery, 1980; Musicant and Butler, 1984;Oldfield and Parker, 1986). Moreover, distortions of the shape of the external ear, which modify its transfer function, result in substantial deterioration in sound localization accuracy Oldfield and Parker, 1984;Humanski and Butler, 1988).…”
Section: General Discussion: Acoustic Cues For Sound Localizationmentioning
confidence: 97%
“…For example, spectral cues to sound location have been invoked to account for the accuracy of localization by monaural listeners (Harris and Sergeant, 1971; Butler and Flannery, 1980; Musicant and Butler, 1984;Oldfield and Parker, 1986). Moreover, distortions of the shape of the external ear, which modify its transfer function, result in substantial deterioration in sound localization accuracy Oldfield and Parker, 1984;Humanski and Butler, 1988).…”
Section: General Discussion: Acoustic Cues For Sound Localizationmentioning
confidence: 97%
“…In a recent study, patients with severe acquired unilateral conductive hearing loss showed improved horizontal localization ability when rehabilitated with BCHA (Agterberg et al, 2011). We note that such results do not prove the use of binaural information, as monaural information can be used to some extent for localization tasks (Oldfield and Parker, 1986). The Agterberg et al study did not include any additional binaural test as, for example, spatial release from masking.…”
Section: Introductionmentioning
confidence: 99%
“…The relative importance of the interaural spectral cues to the localization of sound sources at different elevations is hard to generalize since it varies with the lateral position of the sound source (e.g., Jin et al, 2004). Oldfield and Parker (1986) demonstrated that monaural localization in the vertical plane, which does not take advantage of the interaural spectral cues, is 15 relatively good but somewhat less accurate than binaural localization. Similar data were reported by Humanski and Butler (1988) and Slattery and Middlebrooks (1994).…”
Section: Monaural Cuesmentioning
confidence: 99%